(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the analysis of scientific and methodological issues of increasing the efficiency of teaching philosophical and social sciences in the education system. It is based on the complex, contradictory socio-economic changes taking place in the life of a modern person, problems and vices of various levels and scale, due to the lack of spirituality of modern societies, insufficient teaching of philosophical and social sciences, which play an important role in overcoming it. In this regard, the theoretical and practical work carried out in Uzbekistan, their political and legal documents and scientific sources are analyzed, and the necessity and importance of teaching these subjects in the country’s higher education system is shown. At present, based on the analysis of the problems posed in the article, conclusions and recommendations have been made on the training of qualified personnel for the social and humanitarian sphere in Uzbekistan.